A Model of Adaptive E-Learning System Based On Thinking and Learning Style - Saheli D, Bobade; Poonam A, Manjare (International Journal of Computer Sciences and Engineering, 2015)
This paper discusses the design of adaptive learningSystem based on student’s learning styles. The system adaptively is based on two learning style models, which are VAK and Felder. The VAK learning styles include visual, auditory, and kinesthetic, while the Felder learning styles include global and sequential. This system will combine these learning styles to alter its course presentation to each student. The system extends the advantages of conventional e-learning which are classroom and platform independence.